Echoes of Change: Tracing Phonological Shifts in the Ibanag Language - Matammu, Corazon (International Journal of Arts, Sciences and Education, 2024)
Abstract This study investigated the phonological features of the Ibanag language, focusing on significant phonetic changes occurring in naturally-occurring spoken data across seven Ibanag-speaking municipalities in Northern Luzon. The research aimed to fill the gap in the linguistic literature by analyzing how the language’s phonology has evolved particularly concerning vowel loss, vowel change, diphthong change, consonant change, and metathesis. The findings reveal several key patterns in Ibanag phonology. Vowel loss is notably prevalent when prefixes are attached to base words beginning with the vowel a-. Additionally, vowel change occurs in two primary instances such as when prefixes combined with the vowel i- result in an e- sound, and when prefixes combined with u- lead to an o- sound. Diphthong changes are evident in the spoken register, where final diphthongs -ay and -aw often reduce to -e and -o, respectively. Consonant changes are also observed, particularly in the replacement of t- and d- with s- or z- in certain infixed verbs, reflecting a dynamic shift in oral usage. Furthermore, metathesis occurs when words are prefixed with causative affixes in their perfective forms. These findings contribute to a deeper understanding of the Ibanag language’s phonological structure and its ongoing evolution, providing valuable insights into the linguistic diversity within the Northern Philippine region. Keywords: Consonant change, diphthong change, Ibanag, metathesis phonological changes, vowel loss